Observasi dan Penerapan Kaidah Arsitektur Islam pada Masjid-Masjid di Kota Kendari - Muhammad Arbi’Uzzakir J.; Apria Safitri Pratiwi; La Pande Jurumai (Jurnal Inovasi Sains dan Teknologi (INSTEK), 2023)
Islamic architecture is a concept of Islamic thought originating from the Al-Qur'an, As-Sunnah, the Prophet's Family, the Prophet's Companions, Muslim Scholars and Scholars. The purpose of this study is to find out the application of Islamic architectural principles to mosque buildings in the city of Kendari. This study used the Field Research method which was carried out using observation techniques and conducting interviews and documentation. The results of this study reveal the fact that the application of Islamic architectural principles to several mosques in the city of Kendari is mostly applied through ornaments such as calligraphy, geometric shapes, arch forms, etc. And its application is in accordance with the rules that exist in Islam.